School Public Relations (PR) Strategy in Building Partnerships with the Multicultural Identity in Maluku Community in Ambon City - Dwi Kurnianing Ratri; Perawati Silalahi; Akhmad Suyatno; Iklima Titawael (CV. Ksatria Siliwangi, 2026)
Effective school public relations (PR) play a strategic role in strengthening school–community partnerships that support educational quality and institutional sustainability. Although numerous studies have explored school–community collaboration, limited attention has been given to public relations strategies grounded in the multicultural identity and local wisdom of post-conflict communities such as Ambon, Indonesia. This study aims to analyze school public relations strategies for developing effective partnerships within the multicultural context of Ambon City, Maluku Province. A qualitative literature review with a descriptive-analytical approach was employed by examining books, peer-reviewed journal articles, conference proceedings, and educational policy documents related to school public relations, community partnerships, multicultural education, and Maluku local wisdom. The findings reveal six major strategies for strengthening school–community partnerships: (1) involving community and religious leaders as trusted partners, (2) developing school programs based on Maluku cultural values, particularly pela gandong, (3) implementing inclusive and sustainable two-way communication, (4) utilizing digital communication and social media strategically, (5) establishing partnerships with local government, religious organizations, and community institutions, and (6) strengthening the role of school committees as institutional bridges. These findings highlight that culturally responsive public relations practices contribute significantly to building trust, promoting social cohesion, and enhancing educational collaboration in multicultural communities. This study offers practical recommendations for school leaders and educational policymakers in designing culturally grounded public relations strategies applicable to multicultural educational settings.